La2NiO4+δ as cathode for SOFC: Reactivity study with YSZ and CGO electrolytes - Montenegro Hernandez, Alejandra (2010)
In this work was studied the electrochemical response of La2NiO4þd compound by impedancespectroscopy measurements. This compound is a potential cathode material to beused in Solid Oxide Fuel Cell (SOFC). The area specific resistances (ASR) of a La2NiO4þd/YSZ/La2NiO4þd symmetrical cell were determined between 600 and 800 C. The ASR valuesincreases with time suggesting a chemical reaction between the cells components.Reactivity studies were carried out between La2NiO4þd and both YSZ and CGO electrolytes.The reactivity studies were performed by means of two different tests: La2NiO4þd filmsdeposited onto both electrolytes and heated at 900 C for 72 h (Pellet Test), and intimatemixture of La2NiO4þd with either YSZ or CGO powders were heat treated at 900 C during 2 h(Powders Test). In each case the reaction products were evaluated by XRD. Both studiessuggest a high reactivity between the electrode (La2NiO4þd) and the electrolytes (YSZ, CGO).